The link between varicella and immune system: which children will develop acute cerebellitis? - Elena Bozzola; Rita Carsetti; Eva Piano Mortari; Marco Masci; Giulia Spina; Alberto Villani (BMC, 2020)
Abstract Introduction Varicella may complicate with cerebellitis in previously healthy children, requiring hospitalization. Aim of our study was to define whether children who experienced varicella cerebellitis have a normal immune system. Methods Patients over 3 years of age admitted at Bambino Gesù Children from January 2006 till June 2016 for cerebellitis in varicella were asked to participate to the follow-up study. The immune status was evaluated clinically and by laboratory investigations. Results Twenty-five patients were included in the study. At follow up, at least one immunological alteration was detected in 80% of patients. To avoid bias due to possible effects of the recent disease, we separately analyzed patients who had the follow-up control at least 1 year (Group 1) or between 1 month and 1 year (Group 2) after the hospitalization for acute varicella cerebellitis. The results were similar in both groups with immunological alterations detected in 84,6 and 75% of the patients, respectively. Conclusions Our preliminary results indicate that sub-clinical immunological defects may correlate to cerebellitis in varicella.